A case of a large pedunculated-type osteochondroma from late medieval Ilok, eastern Croatia: Bioarchaeological, paleoradiological and histological study. (October 2022) - Čavka, Mislav; Erjavec, Igor; Seiwerth, Sven; Carić, Mario; Janković, Ivor; Krznar, Siniša; Rimpf, Andrea; Brkić, Hrvoje; Pavičin, Ivana Savić; Vodanović, Marin; Novak, Mario
Highlights: First case of a large fibular osteochondroma from archaeological contexts. Studied through a combination of (bio)archaeology, radiology and histology. CT-guided biopsy as a new analytical approach for study of ancient bone neoplasms. Abstract: Osteochondroma or osteocartilaginous exostosis is one of the most common benign tumors of the bone. Causes for the disease are yet unknown, but there are indications that they may be linked to abnormality in the growth plate and possibly mutation in EXT1, EXT2 and EXT3 genes. Cases of reported osteochondromas range from prehistoric to contemporary examples, are not limited geographically, and no evidence for sex predominance has been reported. Here we present a unique case of large pedunculated-type osteochondroma on the right fibula of an adult female skeleton from the medieval site of Ilok-Krstbajer in eastern Croatia. In order to gain more insight into this pathological change we used holistic approach consisting of a combination of techniques that have not been used previously in the analysis of neoplasms from archaeological settings. The cauliflower-shaped growth is 50 mm long in sagittal and 57.41 mm in transverse diameter with the tumor exhibiting a bulbous, rough superior surface, and a flat, smoother inferior surface. The gross morphology of the tumor together with radiological and histopathological features support the diagnosis of a proximal fibular osteochondroma making it the first such case in an archaeological population. Based on archaeological context and similar clinical cases it seems that the presented osteochondroma did not have major impact on the life-quality of a woman affected by this pathology. The procedure used in this study is minimally invasive and highly accurate, and as such sets new analytical criteria for studies of ancient bone neoplasms.